Imaging on the painful and compressed nerve: lower extremity - Marcelo Bordalo (17704395) (2025)
Entrapment neuropathies of the lower extremity are often underdiagnosed due to limitations in clinical examination and electrophysiological testing. Advanced imaging techniques, particularly MR neurography and high-resolution ultrasonography (US), have significantly improved the evaluation and diagnosis of these conditions by enabling precise visualization of nerves and their surrounding anatomical structures. This review focuses on the imaging features of compressive neuropathies affecting the lumbosacral plexus and its branches, including the femoral, obturator, sciatic, common peroneal, and tibial nerves. Key conditions such as meralgia paraesthetica, piriformis syndrome, and tarsal tunnel syndrome are discussed, highlighting findings such as nerve thickening, T2 hypersignal, fascicular changes, and associated muscle denervation patterns. The ability to detect structural causes, including anatomical variations, fibrous bands, and space-occupying lesions, underscores the value of these imaging modalities in facilitating early diagnosis, guiding therapeutic interventions, and improving patient outcomes. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00264-025-06419-1